Factors affecting the occurrence of maxillary sinus fungus ball - Jang, Hye-Bin; Lee, Dong Hoon; Lim, Sang Chul (Frontiers in Surgery, 2024)
ObjectiveWe identified patients who initially did not have a maxillary sinus fungus ball on computed tomography (CT) but developed it on a subsequent CT scan. We assessed potential risk factors for developing a maxillary sinus fungus ball between the two scans.Patients and methodsThis study included 35 patients with 38 lesions who initially had no maxillary sinus fungus balls on CT but were later diagnosed with the condition and underwent surgery.ResultsWe analyzed 38 lesions in 35 patients, each of whom had normal CT scan results initially but later developed a maxillary sinus fungus ball. No specific risk factors for developing a maxillary sinus fungus ball were identified. However, when compared to the maxillary sinusitis group, facial trauma and dental implant surgery appeared to be associated with maxillary sinus fungus ball formation (p < 0.05).ConclusionWe investigated factors influencing the development of maxillary sinus fungus balls that were absent in previous CT scans and found no significant risk factors. Nonetheless, relative to the maxillary sinusitis (control) group, the maxillary sinus fungus ball group tended to have more previous facial trauma and dental implant surgery.